Behavioral Inhibition in Childhood: European Portuguese Adaptation of an Observational Measure (Lab-TAB) - Luís Faísca; Laura I. Ferreira; Catarina C. Fernandes; Jeffrey R. Gagne; Ana T. Martins (MDPI AG, 2021)
The assessment of behaviorally inhibited children is typically based on parent or teacher reports, but this approach has received criticisms, mainly for being prone to bias. Several researchers proposed the additional use of observational methods because they provide a direct and more objective description of the child's functioning in different contexts. The lack of a laboratory assessment of temperament for Portuguese children justifies the adaptation of some episodes of the Laboratory Temperament Assessment Battery (Lab-TAB) as an observational measure for behavioral inhibition. Method: In our study, we included 124 children aged between 3 and 9 years and their parents. The evaluation of child behavioral inhibition was made by parent report (Behavioral Inhibition Questionnaire) and through Lab-TAB episodes. Parental variables with potential influence on parents' reports were also collected using the Social Interaction and Performance Anxiety and Avoidance Scale (SIPAAS) and the Parental Overprotection Measure (POM). Results and Discussion: The psychometric analyses provided evidence that Lab-TAB is a reliable instrument and can be incorporated in a multi-method approach to assess behavioral inhibition in studies involving Portuguese-speaking children. Moderate convergence between observational and parent report measures of behavioral inhibition was obtained. Mothers' characteristics, as well as child age, seem to significantly affect differences between measures, being potential sources of bias in the assessment of child temperament.